Development of an indicator system for evaluation of quality of undergraduate education in public health: a Delphi study based on CIPP evaluation model - Jiaqi PENG; Jiamin WANG; Gongming LI; Bingsong LI; Yanxiu LIU; Yujia FENG; Xiaojie SUN; Xuemei ZHEN (Zhongguo gonggong weisheng)
ObjectiveTo establish an evaluation indicator system for the quality of undergraduate training of public health talents, and to provide a basis for the reform of undergraduate teaching in public health and preventive medicine. MethodsBased on the context, input, process, product (CIPP) evaluation model, a preliminary evaluation indicator system was constructed through literature review. Two rounds of Delphi expert consultation were conducted with 15 experts in social medicine and health services, epidemiology, biostatistics, microbial testing, health toxicology and nutrition, and educational management. After the group discussion method was used to determine the indicators of the evaluation system, the analytical hierarchy process was taken to determine the weight of each indicator. ResultsAfter two rounds of consultation, the expert positive coefficient was 100% and the group authority coefficient was 0.746 and 0.789, respectively. After the second round of consultation, the Kendall coordination coefficient W of the primary and secondary indicators increased to 0.297 and 0.237, respectively (both P < 0.05). The final evaluation indicator system contains 4 primary, 12 secondary, and 52 tertiary indicators. The weight coefficients of the four primary indicators were 0.233 for context, 0.141 for input, 0.233 for process, and 0.394 for product. ConclusionsThe final indicator system has passed the consistency test and has scientific, comprehensive and good application value, which has guiding significance for the quality evaluation of undergraduate talent training in public health majors. The weight of the indicators suggests that the cultivation of public health talents be in line with social needs, and the strengthening of students' professional identity can better promote the development of the discipline.